Temperature - Schuetz, Kristin (Minneapolis, MN : Bellwether Media, 2016)
"Developed by literacy experts for students in kindergarten through grade three, this book introduces temperature to young readers through leveled text and related photos"--Provided by publisher.
Includes bibliographical references and index.
005-008.
K to Grade 3.
Keywords: Temperature -- Juvenile literature